The Contestation of State, Religious, and Customary Laws on Child Marriage: A Legal Pluralism Perspective - Budiman, Arman; Rumadi; Dli’fain, Alif Faza (UIN K.H. Abdurrahman Wahid Pekalongan, 2025)
Child marriage remains a complex issue within Indonesia’s multicultural legal system. The lack of synchronization among state law, religious law, and customary law creates a significant space for legal contestation, particularly in the practices of marriage dispensation and marital validation (isbat nikah). This study aims to analyze the dynamics of legal contestation among these systems using a normative-empirical legal approach through the examination of legal documents, regulations, and critical legal literature. Employing John Griffiths’ theory of legal pluralism, the study reveals that the Indonesian state tends to adopt a form of weak legal pluralism, recognizing religious and customary laws only to the extent that they do not contradict state law. The primary academic contribution of this study lies in its detailed exploration of how local and religious norms influence judicial decisions regarding dispensation and marital validation—an area that has received limited critical scrutiny in previous studies, which largely focused on formal normative analysis. This research also highlights the inadequacy of uniform national legal policies in responding to the diversity of grassroots social norms. Therefore, it advocates for a reformulation of legal approaches that are more participatory and context-sensitive through inclusive dialogue among state authorities, religious leaders, and customary communities. Such an approach is essential to ensuring the fair and sustainable protection of children’s rights within an adaptive legal pluralism framework that reflects Indonesia’s social realities.